FORMULASI FOOD BAR BERBASIS TEPUNG UBI JALAR UNGU DAN PISANG AGUNG (Musa paradisiaca Formatypica) MASAK - Nurhayati Nurhayati; Nurud Diniyah; Putri Gita Kurniasari (JURNAL AGROTEKNOLOGI, 2018)
Advance in food technology can produce practical food products which are easy to consume. Food Bar is practically product, contain a high-calorie and usually made from a mixture of rich nutrient food using binder to form it into solid and compact. This research aims to determined the quality (sensory and physicochemical) of food bar made from purple sweet potato flour and ripe agung plantain and the best formula of food bar. This study used a completely randomized design with one factor, i.e. composition of purple sweet potato flour and ripe agung plantain. The combination of treatments were consist of P1 (20% purple sweet potato flour and 80% ripe agung plantain cultivar), P2 (30% purple sweet potato flour and 70% ripe agung plantain cultivar), P3 (40% purple sweet potato flour and 60% ripe agung plantain cultivar), P4 ( 50% purple sweet potato flour and 50% ripe agung plantain cultivar) and P5 (60% purple sweet potato purple and 40% ripe agung plantain cultivar). The parameters observed were moisture content, ash content, fat content, protein content, and carbohydrate content as well as the organoleptic properties. The result showed that the interaction of the best food bar by effectiveness testing of the formula was P2. The interaction of food bar with formula of purple sweet potato flour and ripe agung plantain cultivar significantly affected the texture, brightness (L), the value of a* and b*, moisture content, ash content, fat content, protein content, and carbohydrate content. The best food bar formulation (P2) had the characteristics such as 75.22 g/mm of texture value, 43.47 of lightness value (L), 7.67 of a* value, 18.24 of b* value, 12.80% of moisture content, 2.16% of ash content, 25.14% of fat content, 4.33% of protein content, 45.24% of carbohydrate content, while the preferences score of food bar was 3.08 of color, 3.52 of aroma, 3.2 flavor, 3.6 texture, and 3.56 score for and overall preference of the food bar. Keywords: agung var. plantain, physicochemical, purple sweet potato flour, sensory evaluation